Penggunaan Teknologi Artificial Intelligence Untuk Promosi Wisata Budaya Minahasa Di Media Sosial - Rahman Rizal Wonggo; Brave Angkasa Sugiarso; Aurellyan Zihan Suhban; Friska Ester Takasili (Institut Seni Indonesia Padangpanjang, 2025)
Artificial Intelligence; Digital Tourism; Social Media; Cultural promotion; Minahasa The development of Artificial Intelligence (AI) offers new opportunities for promoting cultural tourism through social media. This study aims to explore the use of AI in creating digital content related to Minahasa culture and to understand public perception of its application. A qualitative descriptive method with a digital simulation and online survey approach was employed, involving 30 student respondents aged 18–22 from Manado and surrounding areas. Data were collected through downloading cultural content from Instagram, generating AI-based automatic captions, and distributing online questionnaires to assess respondents’ perceptions. The results indicate that AI can effectively recognize visual elements of Minahasa culture, such as traditional houses, Tinutuan cuisine, and traditional dances, producing captions that are clear, informative, and engaging. Respondents perceived that AI-assisted content can broaden the reach of promotion, enhance content creativity, and facilitate audience understanding of Minahasa culture. However, AI has limitations in capturing non-visual contexts, such as prices, services, local expressions, and specific cultural elements. The majority of respondents agreed that AI should be used as a supportive tool, with human oversight necessary to ensure content authenticity, accuracy, and cultural relevance. This study confirms that AI implementation can improve the effectiveness of digital cultural tourism promotion in Minahasa while maintaining a balance between technological automation and human input to preserve the integrity of local culture.